ANALISIS PENGGUNAAN ARTIFICIAL INTELEGENT (CHAT GPT) DALAM PEMBUATAN MODUL AJAR BAHASA ARAB BERBASIS KURIKULUM MERDEKA - Wahyudi, Kinanti Puspita; Syafi’i, Syafi’i (Program Studi Pendidikan Bahasa Arab Unisda Lamongan, 2025)
This research analyzes the use of Artificial Intelligence (AI), specifically ChatGPT, in the development of Arabic teaching modules based on the Merdeka Curriculum. The purpose of this study is to evaluate the extent to which ChatGPT can produce learning content that matches the unique characteristics of Arabic, including linguistic and cultural aspects. This research was conducted by creating teaching modules for seventh grade students using ChatGPT and analyzing their compliance with Merdeka Curriculum standards. The results show that ChatGPT is able to produce teaching modules with good structure and relevance, but there are still challenges related to accuracy and contextual appropriateness, especially in understanding Arabic grammar (nahwu and sharaf) and cultural aspects. Therefore, although AI can help teachers in lesson planning and preparation of teaching materials, further supervision and adjustments are needed to maintain the validity and relevance of the materials. The main finding of this study is the importance of human-AI collaboration in optimizing AI-generated materials. While ChatGPT provides efficiency in content generation, human intervention is essential for fine-tuning linguistic accuracy and cultural contextualization. This concept of collaboration supports the theory of Human-AI Collaborative Teaching Material Development, which emphasizes that AI serves as an auxiliary tool in structuring and systematizing teaching materials, while humans act as the author.